Strategi Human Capital di Era Disrupsi AI: Systematic Literature Reviews tentang Reskilling, Upskilling, dan Pengelolaan Talent - Endra, Sumarta; Rosi, Vevia; Widiasari, Zulfeni; Syafrita, Willa Kurnia Eka; Pranata, M. Yogi Eka; Syafwandi (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to examine the development and impact of artificial intelligence adoption across various sectors, with a focus on higher education, creative industries, and business. Using bibliometric analysis, this research analyzes relevant articles published between 2021 and 2024, considering citation counts and contributions to understanding AI in different fields. The most cited article is Developing a model for AI Across the curriculum, which discusses the integration of AI in higher education to enhance AI literacy. Additionally, the study highlights the importance of upskilling and reskilling in multinational corporations, as discussed in Rebooting employees: upskilling for artificial intelligence in multinational corporations, emphasizing the need for skill updates to adapt to technological advancements. The research also identifies that AI adoption by SMEs and other industries has significant potential to improve productivity and business sustainability, although challenges related to human resource readiness and digital infrastructure persist. Overall, the findings provide insights into AI's technological development and its implications for business transformation and learning strategies in the digital era.